2019
DOI: 10.3390/joitmc5010013
|View full text |Cite
|
Sign up to set email alerts
|

Operational-Efficiency Improvement of Public R and D Management Agencies in South Korea

Abstract: Public R and D management agencies have been taking on key roles in the national R and D ecosystem. The purpose of this study is to suggest ways to improve the operational efficiency of public R and D management agencies based on analysis of their current status. We approached this study from a life-cycle perspective as it applies to the plan-management evaluation of R and D. Data-collection sources included documents, surveys, and interviews with staff members in agencies responsible for national R and D mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The private sector ( about 80% of all R&D spending) is starting to play an increasingly important role due to the pandemic. The growth rate and volume of private investment significantly exceed public funding [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…The private sector ( about 80% of all R&D spending) is starting to play an increasingly important role due to the pandemic. The growth rate and volume of private investment significantly exceed public funding [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…First, this paper aims to examine the functions and roles of R&D management agencies, which are the main actors of planning and evaluation costs. According to Hong et al (2018) [5] and Hwang et al (2019) [6], as shown in Figure 1, the management and coordination mechanism of national R&D projects can be divided into pan-ministries, science and technology-related ministries, supporting organizations, and industry-university-research institutes. Supporting organizations herein refer to R&D management agencies, which receive their R&D budget from the government, and manage and execute them.…”
Section: Overview Of Public Randd Management Agenciesmentioning
confidence: 99%
“…Park et al (2011) [27] assessed the efficiency of R&D projects supported by the government in scientific and technological areas such as papers and patents by utilizing science and technology investment and performance data of NTIS (National Science and Technology Information Service). Hwang et al (2019) [15] suggested improving the efficiency of public R&D through the improvement of the royalty system. Hwang et al (2019) [6] suggested improving the pro-ductivity of public R&D by improving the operational-efficiency of public R&D agencies.…”
Section: The Role Of Public Randd Agencies As the Engine Of Open Innovation Found From Dea Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, R&D investments and their plan such as technology roadmap also have become more important to maintain the performance of national innovation activities [4]. Especially, R&D management agencies and policies have been taking on important roles in the national R&D environment [5,6]. In the recent era of open innovation, efficient R&D investment at the national level has a greater impact on the development of national competitiveness [7][8][9].…”
Section: Introductionmentioning
confidence: 99%